High-protein goat's milk diet identified through newborn screening: clinical warning of a potentially dangerous dietetic practice. Issue 15 (24th July 2017) - Maines, Evelina; Gugelmo, Giorgia; Tadiotto, Elisa; Pietrobelli, Angelo; Campostrini, Natascia; Pasini, Andrea; Ion-Popa, Florina; Vincenzi, Monica; Teofoli, Francesca; Camilot, Marta; Bordugo, Andrea
Abstract: Objective: Breast-feeding is an unequalled way of providing optimal food for infants' healthy growth and development and the WHO recommends that infants should be exclusively breast-fed for the first 6 months of life. For mothers who are unable to breast-feed or who decide not to, infant formulas are the safest alternative. Despite recommendations, it is possible that parents make potentially harmful nutritional choices for their children because of cultural beliefs or misinformation on infant nutrition. We describe a possible health risk of not breast-feeding, highlighting a potentially dangerous dietetic practice. Design/Setting/Subjects: We report the case of a newborn who was fed with undiluted goat's milk because her mother could not breast-feed and was not aware of infant formulas. Results: The dietary mistake was detected because of a positive expanded newborn screening result, characterized by severe hypertyrosinaemia with high methionine and phenylalanine levels, a pattern suggestive of severe liver impairment. The pattern of plasma amino acids was related to a goat's milk diet, because of its very different composition compared with human milk and infant formula. Conclusions: Our experience demonstrates that, when breast-feeding is not possible or is not exclusive, infants may be at risk of dangerous nutritional practices, including diets with very high protein content, such as a goat's milk diet. Families of not breast-fed infants may need appropriate advice on safe alternatives for infant nutrition to avoid the risks of inappropriate diets.